HUBUNGAN PEMBERIAN REWARD DAN PUNISHMENT DALAM PEMBELAJARAN AQIDAH AKHLAK DENGAN KECERDASAN EMOSIONAL SISWA KELAS VII MADRASAH TSANAWIYAH NEGERI BINJAI - hadist purba (Hijri, 2018)
Research aims for 1. To find out the relationship between the giving of the Reward with the emotional intelligence of students in State Ment of the city; 2). To find out the relationship between the awarding of Punishment with the emotional intelligence of students in State Ment of the city; 3). To find out the relationship between the giving of Reward and Punishment with the emotional intelligence of students in the City State Ment. The population in this research is all grade VII Mts Country Binjai as much as 266 students. Sampling of 40 students was based on the determination of the number of samples table of the student population by 10%. The method research in this thesis using a quantitative approach that put more emphasis on data statistic numbers – numbers. While the method of data collection by using the scale of the attitude of the dam documentation. Prior to analysis, the data is first held testing requirements analysis which includes: test of normality, test linearity, and test its homogeneity. Data were analyzed with the correlation analysis technique of double counting advance correlation product mement of Pearson significance level 0.05From the results of this research can be found some things namely as follows: 1) there is a significant and positive relationship between the giving of the reward with the emotional intelligence of students in learning the morals of Aqeedah in Binjai Country with Mts the coeffic. ient of correlation of 0.736 by category. I.e. between 0.60 – 0.799. 2.) there is a positive and significant relationship between awarding punishment with the emotional intelligence of students in learning the morals of Aqeedah in Mts Country Binjai with coefficient of correlation of 0.990 with very strong category, i.e. between 0.80 – 1.00; 3) There is a positive and significant relationship together – either between the giving of reward and punishment against the emotional intelligence of students in learning the morals of Aqeedah in Binjai Country with Mts Fhitung > F table or 815 > 3.25. These results show that between reward and punishment with the emotional intelligence of the students there are relationships that are relevantKeywords: Reward And Punishment, Of Morals Aqeedah, EmotionalIntelligence